PUBLIC-PRIVATE PARTNERSHIP IN THE CONTEXT OF EVOLUTION OF PUBLIC CONSCIOUSNESS - Andrey E. Berezin; Natal’ya V. Gorodnova; Anastasia A. Peshkova (Статистика и экономика)
The purpose of this study is to study the evolution of social consciousness in the Russian Federation, determining the relationship of the change of paradigm of economic development and the evolution of society, with the development of the Institute for public-private partnership (PPP). The result of this research is to identify the prospects of building in Russia a socially oriented economy, the definition of performance indicators of state economic policy, which promotes the use of PPPs